Whole-Genome Re-Sequencing of Corylus heterophylla Blank-Nut Mutants Reveals Sequence Variations in Genes Associated With Embryo Abortion - Cheng, Yunqing; Jiang, Siqi; Zhang, Xingzheng; He, Hongli; Liu, Jianfeng (Frontiers in Plant Science, 2019)
Yield loss in the economically important hazelnut (Corylus spp.) occurs through the frequent formation of blank nuts. Although the condition is associated with embryo abortion, we have not yet identified the regulatory genes involved. Therefore, this study aimed to determine the genes related to embryo abortion in hazel. We performed whole-genome re-sequencing and single nucleotide polymorphism (SNP) analysis on four mutant hazelnut trees (Empty1 to Empty4, C. heterophylla) bearing blank nuts and four wild-type trees (Full1 to Full4, C. heterophylla). A paired comparison of Empty1 vs. Full1, Empty2 vs. Full2, Empty3 vs. Full3, and Empty4 vs. Full4, along with the intersection of Empty1 to Empty4, revealed 3 081 common SNPs in the four blank-nut mutants. Of these, 215 synonymous SNPs in exonic regions were distributed across 178 candidate genes. Heterozygosity analysis showed that average homozygous and heterozygous SNP ratios were respectively 0.409 and 0.591 in the samples. According to Gene Ontology classification, candidate genes were enriched in the categories of binding, catalysis, molecular transducer, transporter, and molecular function regulator. Among these, 18 of 178 genes had homozygous SNPs in Empty1–4. Cis elements in the promoter region of starch synthase 4 (SS4) contain the RY-element, implying seed-specific expression. Starch granules were absent from Empty1–4 cotyledon cells, but abundantly present in Full1–Full4 cotyledon cells. The blank-nut phenotype has heavier nut shells. Overall, we conclude that single nucleotide variants of Acetyl-CoA carboxylase 1 (ACC1), intracellular sodium/hydrogen exchanger 2 (NHX2), UDP-glycosyltransferase 74E2 (UGT74E2), DEFECTIVE IN MERISTEM SILENCING 3 (DMS3), DETOXIFICATION 43 (FRD3), and SS4 may induce embryo abortion, leading to blank-nut formation. Our results will benefit future research on how the gain or loss of candidate genes influences seed development. Moreover, our study provides novel prospects for seedless cultivar development.